The measurement of economic and social performance - Moss, Milton; Princeton University; Conference on Research in Income and Wealth (New York: National Bureau of Economic Research; distributed by Columbia University Press, 1973)
This volume of Studies in Income and Wealth contains the papers presented at the Conference on the Measurement of Economic and Social Performance held November 4-5, 1971, at Princeton University
Conference held Nov. 4-5, 1971, under the joint sponsorship of Princeton University's Dept. of Economics, and the Conference on Research in Income and Wealth.
Includes bibliographical reference.
osa; 03/10/17
Loans
Keywords: National income; Social indicators